A Rapid and Eco-Friendly Method for Determination of Hydrolysable Tannins and Its Application to Honey Samples - Catelani, Tiago Augusto [UNESP]; Bittar, Dayana Borges [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Springer Nature, 2016)
This paper describes the development of a rapid and clean method for the determination of hydrolysable tannins in honey samples, focusing on an easy and green sample pretreatment and low generation of waste. The proposed method is based on the reaction between KIO3 and hydrolysable tannin compounds in acetate buffer medium (pH 4.75), with formation of a colored product measured at 525Â nm. The analytical conditions were optimized using experimental design (central composite design). The linear range obtained was 40.0–740Â mgÂ L−1 (r = 0.998), and the detection (LOD) and quantification (LOQ) limits were 12.2 and 40.8Â mgÂ L−1, respectively. Acetate buffer was used to ensure formation of the colored product obtained by reaction between the chromogenic reagent and the analyte. The method showed good results when applied to honey samples, with recoveries in the range of 78.3–96.1Â %, and the use of diffuse reflectance spectroscopy coupled with spot test analysis provided low reagent consumption and minimized waste generation. The results obtained with the proposed method were confirmed by a spectrophotometric method.
Keywords: Diffuse reflectance spectroscopy; Eco-friendly method; Honey; Hydrolysable tannin